The concept and significance of registration and permit-licensing procedures in the activities of the National Police - О. А. Bud (Law and Safety)
The absence of sufficient theoretical developments regarding the essence and content of registration, permit and license procedures provided by the National Police of Ukraine is emphasized. In this regard, the following research tasks were formulated: 1) to establish the specificity of the legal nature of registration and permit-licensing procedures as a public service activity of police bodies; 2) determine the content of the categories “services” and “administrative services”, as well as outline their characteristic features. The implementation of the outlined tasks is aimed at achieving the goal, which consists in forming the author’s definition of the concept of “registration and permit-licensing procedures in the activities of the National Police” and clarifying their significance for ensuring the functioning of the permit system.